Boosting Students’ Speaking Skill Through Information Gap Activities (IGA) - Mahmudah, Listiana Eka Dewi; Anggreni, Afrillia; Dewi, Anjar Kusuma; Marhum, Mochtar (Universitas Pahlawan Tuanku Tambusai, 2025)
Speaking proficiency is essential for academic and social development of EFL students. However, numerous students often struggle with limited vocabulary, grammatical deficiencies, and a lack of confidence which contribute to their speaking performance. Therefore, this study exposes the effectiveness of Information Gap Activities (IGA) to elevate students’ speaking skills – specifically in fluency and comprehensibility – of eleventh-grade students at SMA Negeri 1 Sigi. A quasi-experimental design was employed, involving two groups: an experimental class received IGA treatment and a control class taught by using conventional methods, with a total of 60 student participants. Both groups were given pre-tests and post-tests to measure their speaking ability before and after the treatment. Pre-test and post-test data were analyzed using SPSS. The results revealed a statistically significant improvement in the experimental group, with the mean score increasing from 41.67 to 67.50, compared to the control group’s increase from 41.67 to 50.56. The Wilcoxon Signed-Rank Test (p = 0.000) and Mann-Whitney U Test (p = 0.000) confirmed this difference to be statistically significant. These findings suggest that Information Gap Activities can effectively enhance students’ speaking abilities, offering a communicative and interactive alternative to traditional instructional approaches.